Papal jurisprudence c. 400: sources of the Canon law tradition - D'Avray, D. L. (Cambridge University Press, 2019)
State of research : Caspar and after -- Texts and manuscripts -- Rituals and liturgy -- Status hierarchy -- Hierarchy of authority -- Celibacy -- 'Bigamy' -- Marriage -- Monks and the secular clergy -- Heretics : Novatians, Bonosians, and Photinians -- Heretics : in the shadow of St Augustine -- Penance.